2020
DOI: 10.1155/2020/8345235
|View full text |Cite
|
Sign up to set email alerts
|

TILs and Anti-PD1 Therapy: An Alternative Combination Therapy for PDL1 Negative Metastatic Cervical Cancer

Abstract: Background. We investigated the efficacy of TILs and anti-PD1 combination therapy in patients with metastatic cervical cancer with low MSI expression and PDL1-negative. Methods. A total of 80 patients were put on TILs and anti-PD1 combination therapy, and the progression-free survival time (PFS) and overall survival time (OS) were assessed by Kaplan–Meier analysis. Univariate and multivariate analyses were performed to identify factors that could predict the prognosis of metastatic cervical cancer in the previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…25,26 Recent studies have reported that combining anti-PD1 with TIL therapy may confer more effective antitumour effects on metastatic cervical cancer (SCC cases = 65; adenocarcinoma cases = 15). 27 The NLR probably represents the activity of myeloid-derived suppressor cells, which hinder T cell proliferation. 28 The usefulness of NLR as a prognostic biomarker in patients with various solid tumours who received immune checkpoint inhibitors has been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Recent studies have reported that combining anti-PD1 with TIL therapy may confer more effective antitumour effects on metastatic cervical cancer (SCC cases = 65; adenocarcinoma cases = 15). 27 The NLR probably represents the activity of myeloid-derived suppressor cells, which hinder T cell proliferation. 28 The usefulness of NLR as a prognostic biomarker in patients with various solid tumours who received immune checkpoint inhibitors has been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to ICB, TIL ACT tends to be effective against tumors containing viral antigens. It has been reported that patients with HPV-positive metastatic cervical cancer were significantly more likely to respond to TIL ACT as compared to HPV-negative patients (129). In another study, three out of nine cervical cancer patients responded to treatment with TILs that were pre-selected for reactivity to HPV (136).…”
Section: Viral Infectionsmentioning
confidence: 90%
“…TILs are associated with a significantly positive clinical outcome in cervical cancer. They have been identified for tumor specificity, extracted from resected tumor tissue and proliferated ex vivo in media containing cytokines [47,48]. Adoptive T cells have been observed to induce tumor regression at a greater rate than vaccinated lymphocytes [49,50].…”
Section: Adoptive T-cell Therapymentioning
confidence: 99%
“…These modified receptors are capable of recognizing specific MHC antigens [52]. Hence, T-cell receptor therapy involves selecting and targeting specific intracellular and extracellular antigens by modified T-cell receptors, in contrast to TIL therapy, where endogenous tumor-directed lymphocytes are chosen [48]. The modified receptor cells are reinfused into patients, where they induce tumor cell lysis through cytokine production.…”
Section: Genetic Modification Of T Cellsmentioning
confidence: 99%